1999
DOI: 10.1182/blood.v94.12.4093
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Requirements for Optimal Growth and In Vitro Expansion of Human CD34+CD38− Bone Marrow Long-Term Culture-Initiating Cells (LTC-IC), Extended LTC-IC, and Murine In Vivo Long-Term Reconstituting Stem Cells

Abstract: Recently, primitive human bone marrow (BM) progenitors supporting hematopoiesis in extended (>60 days) long-term BM cultures were identified. Such extended long-term culture-initiating cells (ELTC-IC) are of the CD34+CD38− phenotype, are quiescent, and are difficult to recruit into proliferation, implicating ELTC-IC as the most primitive human progenitor cells detectable in vitro. However, it remains to be established whether ELTC-IC can proliferate and potentially expand in response to early acting cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…We have recently demonstrated that Lin − Sca1 + c-kit + cells cultured under serum-free conditions in the presence of K36, undergo self-renewing cell divisions and preserve their ability to short- and long-term multilineage reconstitute lethally irradiated mice 2425. Thus, Lin − Sca1 + c-kit + cells were cultured under such self-renewing conditions in the absence or presence of TNF-α and/or Jo2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have recently demonstrated that Lin − Sca1 + c-kit + cells cultured under serum-free conditions in the presence of K36, undergo self-renewing cell divisions and preserve their ability to short- and long-term multilineage reconstitute lethally irradiated mice 2425. Thus, Lin − Sca1 + c-kit + cells were cultured under such self-renewing conditions in the absence or presence of TNF-α and/or Jo2.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β has been shown to accelerate depletion of HSCs under in vitro culture conditions which themselves result in loss of HSC activity 5051, making it difficult to distinguish between effects on self-renewal and other mechanisms. Recent developments have now made it possible to study HSC self-renewal and its regulation in vitro 24252627. Through such studies, a number of growth stimulatory cytokines have been shown to promote HSC self-renewing cell divisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toward this, great deals of efforts were devoted to develop cytokine cocktails and culture protocols that support the expansion of HSCs and HPCs ex vivo to increase the cell dose available for the transplantation. [21][22][23][24][25][26] This strategy rapidly gained popularity given that the proliferative potential of UCB HPCs far exceeds that of their adult counterpart (reviewed in Mayani and Lansdorp 27 ). The governing principle behind this strategy is that ex vivo expansion of HPCs should accelerate hematopoietic recovery based on the infusion of a greater quantity of HPCs and the fact that these cells have already begun the process of differentiation, thus reducing the length of time required for mature cells to be released to the periphery.…”
Section: Strategies To Improve Hematological Recoverymentioning
confidence: 99%